The influence of brand experiences on consumer-based brand equity - Pina, R.; Dias, Á. (Journal of Brand Management, 2021)
In markets where products and services have become similar, with no major functional differences, and where consumer choices are more and more influenced by emotional aspects rather than by rational thinking, experiences have surfaced as the main form of differentiation between companies. More than the inherent characteristics of products or services per se, brands become a source of differentiation of companies, with its role expanded from an assembly of attributes to a sum of experiences. This investigation in the experiential marketing area aims to understand the dimensions of the experiences that have an influence on consumers, and how do these experiences have influence consumer-based brand equity. Based on a quantitative study, the results show brand experience has a positive influence on consumer-based brand equity. Sensory and emotional experiences evidenced a higher influence in all the dimensions of brand equity. Multigroup analysis also show that intellectual experience triggers brand equity consumers in consumer with positive brand behaviour.